Evolution of scientific productivity in dentistry: tracking postgraduate publications at a Peruvian university - Rojas-Senador, Cesar D.; Garcés-Elías, María Claudia; León-Manco, Roberto A. (Frontiers in Oral Health, 2024)
IntroductionScientific production indicators help universities quantitatively and qualitatively assess postgraduate students’ publications and contribute to the optimization of research processes. This study aimed to determine the frequency of publication in scientific journals of the documents submitted by postgraduate dentistry students to obtain a second professional specialty title and master's and doctoral degrees at a private Peruvian university over seven years.Materials and methodsA cross-sectional study was conducted, considering the population and the records of documents submitted to obtain the second professional specialty title and the master's and doctoral degrees in dentistry at a private Peruvian university, published in its institutional repository from 2017 to 2023. The primary outcome was publication in scientific journals, and the covariates were the year of formal submission of the document, postgraduate level, modality of document preparation, area of dentistry specialty according to the American Dental Association, year of publication, international indexing, impact factor (IF), and quartile. A descriptive analysis was performed to obtain absolute and relative frequencies.ResultsBetween 2017 and 2023, out of 322 documents submitted to receive the second professional specialty title and the master's and doctoral degrees published in the institutional repository, 72 were published in scientific journals. Of these, 81.94% (n = 59) were published in an internationally indexed scientific journal, with 13.56% (n = 8) published in a journal with an IF≥2 and 10.18% (n = 6) in a Q1 category journal.DiscussionIn low-income countries, the nexus between education and scientific output is multifaceted. While education serves as a critical catalyst, numerous challenges constrain the expansion of research. These nations contribute a mere 2% of global scientific production, despite confronting significant public health issues, underscoring a notable discrepancy between educational attainment and research productivity. The disparities in scientific output across universities in Latin America, Asia, and Europe are shaped by a confluence of cultural and economic determinants. In conclusion, 22.36% of the documents submitted to obtain the second professional specialty title and the master's and doctoral degrees by postgraduate dentistry students at a private Peruvian university over seven years were published in scientific journals.